PENGARUH KONSERVATISME AKUNTANSI DAN STRUKTUR KEPEMILIKAN TERHADAP AGGRESSIVE TAX AVOIDANCE (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2011-2015) - B2091151005, KURNIATY (MAKSI UNTAN, 2017)
Financially, the tax is a transfer of resources from the business sector or the business sector to government, so that the company’s payment of taxes is significant cost component and affects profitability. This leads to a desire to reduce the burden of tax paid. Tax aggressiveness is a strategy that still resides in a grey area that is attractive to management for being able to achieve corporate’s and government’s objectives simultaneously. This study aimed to get empirical evidence about the effect of accounting conservatism and ownership structure against aggressive tax avoidance actions on listed companies in the manufacturing sub-sector in 2011-2015. The dependent variable in this study is aggressive tax avoidance proxied by the effective tax rate. While the independent variables are accounting conservatism, institutional ownership, managerial ownership and foreign ownership. This study also had a control variable, they are a return on assets (ROA), debt to total asset ratio (DAR) and capital intensity ratio (CIR). Sampling was done by purposive sampling method with a total of 194 samples from 49 companies for five years. The research result of multiple linear regression analysis showed that accounting conservatism and foreign ownership have a significant negative impact against aggressive tax avoidance. Meanwhile, institutional ownership and managerial ownership have no significant effect on aggressive tax avoidance. Keywords: Effective Tax Rate, Accounting Conservatism, Institutional Ownership, Managerial Ownership and Foreign Ownership.